2018
DOI: 10.1242/bio.031609
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of cyclin B is critical for nuclear division inTrypanosoma brucei

Abstract: Summary statementTrypanosomes do not have a spindle checkpoint but have an ability to regulate the timing of nuclear division by modulating the cyclin B protein level. AbstractKinetoplastids have a nucleus that contains the nuclear genome and a kinetoplast that contains the mitochondrial genome. These single-copy organelles must be duplicated and segregated faithfully to daughter cells at each cell division. In Trypanosoma brucei, although duplication of both organelles starts around the same time, segregation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…In our previous analysis of endogenously YFP-tagged KKT proteins, we noticed that KKT4 localizes not only to kinetochores but also near the poles of the metaphase spindle ( Akiyoshi and Gull, 2014 ). To further examine its cellular localization pattern, we used additional markers on kinetochores (KKT2) and on spindle microtubules (MAP103; Hayashi and Akiyoshi, 2018 ; Fig. 1, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous analysis of endogenously YFP-tagged KKT proteins, we noticed that KKT4 localizes not only to kinetochores but also near the poles of the metaphase spindle ( Akiyoshi and Gull, 2014 ). To further examine its cellular localization pattern, we used additional markers on kinetochores (KKT2) and on spindle microtubules (MAP103; Hayashi and Akiyoshi, 2018 ; Fig. 1, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the molecular basis of MMS-induced metaphase defect, we monitored the degradation kinetics of the mitotic B-type cyclin CYC6, since its degradation is required for metaphase-to-anaphase transition (10). Cycloheximide chase analysis showed that MMS treatment significantly slowed down CYC6 degradation, increasing its half-life from ∼4 to >8 h (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, KKIP5 may act as an upstream factor of the SAC in mediating the DDR for targeting the SAC components to kinetochores. However, whether T. brucei has a SAC is still in doubt (10,35). If there is no SAC, it is unclear how T. brucei maintains genomic stability when kinetochore-microtubule attachment errors occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that KKT4 co-purifies with the APC/C subunits (Akiyoshi and Gull, 2014). Furthermore, although trypanosomes lack a canonical spindle checkpoint (Ploubidou et al, 1999), cells could control the cell cycle progression by regulating the level of cyclin B in the nucleus (Hayashi and Akiyoshi, 2018). We therefore speculate that the interaction between the BRCT domain and the microtubule-binding domain might be governed by the attachment status, which in turn controls APC/C activities and the cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%